Optimization of methods for isolation and culture of primary mouse hepatocytes and establishment of a steatosis model (Jichu yixue yu linchuang)
Objective To improve the isolation and culture methods for primary hepatocytes and to establish a hepatic steatosis cell model for enhancing experimental efficiency and model precision. Methods Improvements were made upon existing techniques for primary hepatocyte cultivation and steatosis model establishment. The technology oriented to optimize the retrograde cannulation and fixation procedures, meticulously calibrating the perfusion speed and duration for mouse liver digestion. The culture medium was supplemented with 2% fetal bovine serum (FBS) during the removal of liver capsules and filtration steps. Additionally, the induction parameters for the steatosis cell model were refined, including the selection of free fatty acid (FFA) types and optimize their concentrations, ratios, and precise induction durations. Results The optimized protocol yielded mouse primary hepatocytes with a viability exceeding 90%, demonstrating ample quantity, favorable morphology, and excellent overall condition. The steatosis cell model exhibited prominent cytoplasmic lipid droplets, impaired glucose and lipid metabolism, as well as mild inflammation and insulin resistance, closely mimicking key aspects of the disease in vivo. Conclusions The refined techniques facilitated the establishment of a stable and physiologically representative in vitro steatosis cell model, which may support further research of pathogenesis of the disease, identification of potential therapeutic targets.